Kunsvoeding en spening van die baba - A.G.W. Nolte (AOSIS, 1979)
Whenever possible mothers should be encouraged to breastfeed their babies. If, however, the mother is unable or unwilling to do so the baby is bottle-fed. The goal of infant nutrition is a well nourished but not over nourished infant. In accomplishing this end, the infant may be either breastfed or artificially fed with cow's milk, evaporated milk, or one of the many prepared formulas that are currently available. This article is also concerned with weaning and the introduction of solid foods.